"Improvement focused" evaluation of place-based initiatives: An approach to examining three methodologies. (June 2018) - Heery, Lauren; Naccarella, Lucio; McKenzie, Rosemary
Place-based initiatives offer a comprehensive, whole-of-community approach to solving complex problems. Impact evaluation of complex initiatives is challenging and alternative "improvement focused" methodologies, such as developmental evaluation, action research, and quality improvement, are being used. Limited understanding exists about how these methodologies work when used in place-based initiatives, which contexts they are individually best suited to, and what they can achieve. This article outlines an approach to examining the application of developmental evaluation, action research, and quality improvement to the evaluation of place-based initiatives. The approach used a realist evaluation methodology and involved a literature review and three "instrumental" case studies. The approach described in this article can support others to design and undertake their own research to inform decision making around the most suitable methodologies in the emerging field of place-based initiative evaluation.